Two new species of Chnoodes Chevrolat (Coleoptera: Coccinellidae) from Brazil - Krüger, Thaysa C.; Castro-Guedes, Camila F.; Almeida, Lúcia M. (Zootaxa, 2016)
Two new species of Chnoodes from Brazil are described: C. machadoi sp. nov. (Holotype male deposited in DZUP: Mato Grosso State, Cáceres muncipality, 13.XI.1984, Buzzi, Mielke, Elias & Casagrande leg.) and C. unimaculata sp. nov. (Holotype female deposited in DZUP: Amapá State, Oiapoque municipality, V.1959, M. Alvarenga leg.). They can be distinguished from all previously described species mainly by the yellowish border of the elytra in C. machadoi sp. nov., and the large mid-dorsal pale spots in C. unimaculata sp. nov. Six species are redescribed: Chnoodes brasiliensis Korschefsky, C. chaudoiri Mulsant, C. discomaculata (Crotch), C. pentagona Crotch, C. pseudosanguinea Brèthes, and C. tarsalis Weise. A key to Brazilian species of Chnoodes and new records are also given.